Faculty Senate, Minutes, October 16, 2008 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2008)
Valdosta State University. Faculty Senate, Minutes, October 16, 2008. Chairperson, Patrick J. Schloss; Vice Chairperson, Louis Levy; Executive Secretary, Barney “Jay” Rickman; Parliamentarian, Cindy Tandy;
1 electronic document. Faculty Senate, Minutes, October 16, 2008. 10 pages.
Keywords: Valdosta State University. Faculty Senate; Minutes (Records); Committees; Electronic records